Legality of General Practitioners in Practicing Acupuncture - Winata, Eurika; Nugraheni, Ninis; Nugroho, Hari Pudjo (Jurnal Indonesia Sosial Sains, 2025)
Regulations for acupuncture practice in Indonesia are based on Law No. 17 of 2023 concerning health and Permenkes No. 34 of 2018 concerning license and practice regulation of acupuncture therapists. In Indonesia, acupuncture treatment consists of traditional acupuncture done by acupuncture therapists and medical acupuncture done by doctors, both acupuncture specialists and general practitioners. This research titled "Legality of General Practitioners in Carrying Out Acupuncture Treatment" aims to analyze the authority of general practitioners in carrying out acupuncture treatment and the liability between general practitioners and patients when carrying out acupuncture treatment. This research uses a normative juridical method with two approaches, namely the statuary approach and the conceptual approach. The results of this research are that currently, in Indonesia, there is a void of norms that regulate the authority of general practitioners in doing acupuncture treatment. Therefore, besides liability in the form of default and acts against the law in the field of civil penal law between doctors and patients, general practitioners can also be held responsible in the field of penal law and administrative penal law.